Nexus Between Energy Poverty, Economic Growth, Ijarah Sukuk and Environmental Degradation in Nigeria - Zainab Dahiru Wowo; Muhammad Mustapha Abdullahi; Ahmed Halliru Malumfashi (Al-Amwal : Jurnal Ekonomi dan Perbankan Syari'ah, 2025)
Introduction: Poor energy access leads to environmental degradation among developing countries in Africa. This study investigated the nexus among energy poverty, economic growth, Ijarah Sukuk and environmental degradation in Nigeria based on time series data covering 1981 to 2023. The study intends to explore the effect of energy poverty, Ijarah Sukuk and economic growth on environmental degradation.Methods: The variables used were environmental degradation (dependent variable), energy poverty, Ijarah Sukuk and economic growth (independent variables). Population growth and capital formation were the control variables. Autoregressive Distributive Lag and Vector Error Correction were concurrently applied.Results: The study found a long run relationship based ARDL Bound test which justifies for both long and short run estimations. The result of long run revealed that energy poverty and Ijarah Sukuk are negatively and significantly related to environmental degradation, while economic growth is positively and significantly associated. Also, the short run, result is consistent to its long run estimates even at 10%. This shows that, an increase in current value of energy poverty and Ijarak Sukuk will decrease environmental degradation but increase by an increase in one-year lag value of energy poverty, while a point growth of economy will increase environmental degradation. Finally, the Vector Error Causality result indicates evidence of uni-directional causality from economic growth and energy poverty in the short run. Therefore, the growth of economy which leads to a reduction in energy poverty will result to higher environmental degradation reflecting two-sided blades of the same razor for Nigeria. Study of this nature reveals how the interplay among poor energy consumption, economic growth and environmental degradation, and concludes that energy poverty and economic growth have significant effect on environmental degradation for Nigeria.Conclusion and suggestion: Finally, it was recommended that, policymakers should prioritize energy poverty reduction strategy through adopting economic growth and environmentally friendly technology policy framework in Nigeria.